Communicating About Water in the Floridan Aquifer Region: Part 4—The Media’s Role in Water Perceptions - Sadie Hundemer; Shenara Ramadan (EDIS)
Local and regional news media often have a major impact on public awareness of and interest in water challenges. It is not simply what the media report that affects public perceptions, but also how they report it. A study of nine years of water reporting from six newspapers in the Floridan Aquifer region revealed a hierarchy of frames used to relate water conditions to human interests. The dominant reasons provided for readers to care about water conditions were economics, human health, and ecosystem impacts (in that order). Ecosystem impacts receive comparatively little journalistic attention, and this may have unintended effects. For example, public interest in water issues may not be as high as it would be if ecosystem impacts were robustly covered. Water news framing can also impact the objectives of water policy. If ecosystem impacts are not emphasized in the media, they may not be adequately attended to in governance.